The Effect of Role Play Technique on Students’ English Speaking Proficiency and Classroom Participation at SMPN 37 Pekanbaru - Annisa Salsabilla; Miranti Eka Putri (Universitas Muria Kudus, 2026)
This study aims to investigate the effect of role play technique on seventh grade students' English speaking proficiency at SMP Negeri 37 Pekanbaru. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group design involving pretest and posttest. The sample consisted of 70 students: 36 students from class VII 7 as the experimental group and 34 students from class VII 6 as the control group, selected through purposive sampling. Data were collected through speaking performance tests assessing five aspects: fluency, pronunciation, vocabulary, grammar, and comprehension. Statistical analysis was conducted using paired samples t-test and independent samples t-test. The findings reveal that the experimental group's mean score increased significantly from 43.41 (pretest) to 62.82 (posttest), with a mean difference of 19.41 points. The paired samples t-test yielded t = -56.544 with Sig. (2-tailed) = 0.000 (p < 0.05), indicating a significant improvement in the experimental group's speaking proficiency after treatment. Furthermore, the independent samples t-test comparing posttest scores between groups showed t = -10.377 with Sig. (2-tailed) = 0.000 (p < 0.05), confirming a significant difference between the experimental group (M = 62.82) and the control group (M = 47.54). These results demonstrate that role play technique significantly and positively affects students' English speaking proficiency. The findings imply that English teachers should consider integrating role play into speaking instruction to create more interactive and communicative learning environments, thereby enhancing students' speaking confidence and proficiency. Additionally, this study provides empirical evidence supporting the use of role play as an effective pedagogical strategy in EFL classrooms and may serve as a reference for future research on interactive language teaching techniques.